2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5628092
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics based assessment of respiratory diseases using GMM classification

Abstract: The focus of this paper is to present a method utilizing lung sounds for a quantitative assessment of patient health as it relates to respiratory disorders. In order to accomplish this, applicable traditional techniques within the speech processing domain were utilized to evaluate lung sounds obtained with a digital stethoscope. Traditional methods utilized in the evaluation of asthma involve auscultation and spirometry, but utilization of more sensitive electronic stethoscopes, which are currently available, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 7 publications
1
25
0
2
Order By: Relevance
“…When results are compared with other approaches [12,28], it was noticeable that classification rates, for supervised proposal, were closer to these results. Table 4 Results from normal signals were poor in the unsupervised training.…”
Section: Discussionmentioning
confidence: 86%
“…When results are compared with other approaches [12,28], it was noticeable that classification rates, for supervised proposal, were closer to these results. Table 4 Results from normal signals were poor in the unsupervised training.…”
Section: Discussionmentioning
confidence: 86%
“…Most respiratory sounds investigated thus far were breathing sounds or lung sounds rather than cough sounds. Second, the GMM-UBM technique has proven its efficiency in respiratory sound classification [39][40][41][42], and has been found to perform reliably, even with small data samples. While some recent studies showed that deep learning approaches such as Convolutional Neural Networks are more efficient for respiratory sound classification (notably lung sounds), these algorithms require a large dataset [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…By experimenting on a public dataset, named R.A.L.E. [9], we show that the detection model performs better than previous works [12,17,20] which use hand-crafted acoustic feature based machine learning model, applied on the same dataset (R.A.L.E. [9].…”
Section: Introductionmentioning
confidence: 96%